Rhythmic Movement Activities Physical Education for Improving Elementary Students’ Fundamental Movement Skills and Enjoyment - Yudiawan, Deri; Gumilang, Eva Sri (LITPAM, 2026)
Elementary physical education often emphasizes general and repetitive physical activities, while the simultaneous development of fundamental movement skills and students’ enjoyment has received limited attention. This study examined the effect of rhythmic movement activities on fundamental movement skills and enjoyment among elementary school students. A quantitative quasi-experimental method with a pretest-posttest control group design was used. The participants were 30 third-grade students at SD Negeri Cikahuripan, Bandung Regency, divided into an experimental group and a control group, each consisting of 15 students. Fundamental movement skills were measured using the Test of Gross Motor Development-2, while enjoyment was measured using the Physical Activity Enjoyment Scale questionnaire. Data were analyzed using descriptive statistics, normality and homogeneity tests, paired sample t-test, and independent samples t-test. The findings showed that the experimental group demonstrated a greater improvement in fundamental movement skills, increasing from 96.80 to 120.20, compared with the control group, which increased from 88.40 to 104.67. The between-group comparison confirmed a significant difference in fundamental movement skills. Enjoyment also increased in both groups, with the experimental group improving from 47.47 to 56.53 and the control group from 44.27 to 52.93, although the between-group difference was not statistically significant. These findings indicate that rhythmic movement activities are effective for strengthening students’ movement competence and have supportive value in creating more enjoyable physical education learning experiences.